Implementation of teaching physical education at institute of sports teacher education - Syed Ali, S.K.; Zahidi, M.A.; Mohamed, M.F.; Ismail, W.; Zailani, M.A. (2015)
This study is about implementation of teaching physical education at institute of sports teacher education (ISTE). Based on the study, the objectives are looking at the teaching of physical education and its impact on the students learning. This study might also provide policy makers with ideas about relevant competencies to the teaching of physical education. This study adopts a descriptive survey with fifty (50) physical education students, thirty (30) physical education lecturers, fifteen (15) head departments and three (3) campus directors. Next, researchers used frequencies and percentages to analyze data from the respondents. Data collected were grouped according to each response and percentage was used for comparison of responses. Based on the findings, the researchers concluded that there was some needs to improve the teaching of physical education in theory and practical lessons. This research revealed that there was no supervision in the ISTEs as far as the teaching of physical education was concerned. It was also noted that those lecturers who taught the subject needed to have some interest in the subject. It was also concluded that physical education students must complete teacher education programs and focused on a health and fitness-related subject.